Comparative prediction of lymph node metastasis in pT1 colorectal cancer among Western and Japanese guidelines - Tanino, Fumiaki; Yamashita, Ken; Morimoto, Shin; Takehara, Yudai; Yamamoto, Noriko; Kamigaichi, Yuki; Nishimura, Tomoyuki; Tanaka, Hidenori; Takigawa, Hidehiko; Urabe, Yuji; Kuwai, Toshio; Shimamoto, Fumio; et al. (Frontiers in Oncology, 2024)
BackgroundAdditional surgery with lymph node (LN) dissection is recommended for pT1 colorectal carcinoma (CRC) resected by endoscopy, based on pathological risk factors for LN metastasis (LNM), according to guidelines by the Japanese Society for Cancer of the Colon and Rectum (JSCCR), National Comprehensive Cancer Network (NCCN), and European Society for Medical Oncology (ESMO).MethodsWe retrospectively analyzed 560 consecutive patients with T1 CRC who underwent endoscopic resection alone (n=190) or initial or additional surgery with LN dissection (n=370) between 1992 and 2017 at Hiroshima University Hospital. Patients were classified into LNM low- and high-risk groups according to guidelines by the JSCCR, NCCN, and ESMO as follows. Patients without any specified pathological LNM risk factor were included in the LNM low-risk group, while the high-risk group comprised all other patients. We analyzed the LNM predictive ability of each guideline.ResultsThe LNM high-risk rate, sensitivity, specificity, positive and negative predictive values, accuracy of LNM risk, and AUC for LNM predictive ability were 82%, 100%, 19%, 9%, 100%, 26% and 0.596 in the JSCCR guidelines; 52%, 98%, 52%, 15%, 99%, 56%, and 0.749 in the NCCN; and 54%, 98%, 50%, 15%, 99%, 54%, and 0.743 in the ESMO, respectively.ConclusionsThe JSCCR guidelines could diagnose LNM in all cases but had the highest false-positive rate. It is important to reduce unnecessary additional surgeries for pT1 CRCs after ER.